The Sphagnum microbiome: new insights from an ancient plant lineage - Kostka, Joel E.; Weston, David J.; Glass, Jennifer B.; Lilleskov, Erik A.; Shaw, A. Jonathan; Turetsky, Merritt R. (The New phytologist, 2016)
Peat mosses of the genus Sphagnum play a major role in global carbon storage and dominate many northern peatland ecosystems, which are currently being subjected to some of the most rapid climate changes on Earth.Arapidly expanding database indicates that a diverse community of microorganisms is intimately associated with Sphagnum, inhabiting the tissues and surface of the plant. Here we summarize the current state of knowledge regarding the Sphagnum microbiome and provide a perspective for future research directions. Although the majority of the microbiome remains uncultivated and its metabolic capabilities uncharacterized, prokaryotes and fungi have the potential to act as mutualists, symbionts, or antagonists of Sphagnum. For example, methanotrophic and nitrogen-fixing bacteria may benefit the plant host by providing up to 20–30% of Sphagnum carbon and nitrogen, respectively. Next-generation sequencing approaches have enabled the detailed characterization of microbiome community composition in peat mosses. However, as with other ecologically or economically important plants, our knowledge of Sphagnum–microbiome associations is in its infancy. In order to attain a predictive understanding of the role of the microbiome in Sphagnum productivity and ecosystem function, the mechanisms of plant–microbiome interactions and the metabolic potential of constituent microbial populations must be revealed.